Mimicking primary processes in photosynthesis photochemistry of covalently linked porphyrin quinones studied by EPR spectroscopy - Speck, Marcus; Kurreck, Harry; Aguirre, Santiago; Dieks, Henrik; von Gersdorff, Jörg; Kay, Christopher W.M..; Bachelor, Stephen N.; Mößler, Johann; Newman, Hans; Niethammer, Dominique; Schlüpmann, Jenny; Sobek, Jens; et al. (Solar Energy Materials and Solar Cells, 1995)
Porphyrin quinones (P-Q's), covalently linked via different aliphatic bridges, have been synthesized and studied in their (porphyrin) cationic and (semiquinone) anionic radical states by EPR, ENDOR and TRIPLE resonance techniques. Time-resolved and steady-state photoexcitation experiments showed that intra- and intermolecular electron transfer (ET) processes occur in these systems, both in isotropic and reversed micellar solution. Analysis of the experimental data showed the occurrence of photochemical redox processes which result in the formation of hydroquinoid and chlorin type derivatives. Strong polarisation effects were observed for the doublet species - generated by intermolecular ET - under steady-state illumination. It is demonstrated that the polarisation pattern can be explained by the encounter of a triplet and a doublet species allowing the radical triplet pair mechanism to occur. Using a porphyrin linked to a redox active crown ether quinone, complexation of sodium cations in the crown gave rise to well resolved sodium ENDOR lines with an unusual high spin density at the alkali metal ion. Moreover, interesting photochemically induced conformational changes, such as folding and unfolding of donor and acceptor with respect to one another in the case of a flexible butylene bridge, could be detected.